2017
DOI: 10.17219/acem/58783
|View full text |Cite
|
Sign up to set email alerts
|

Female and male orbit asymmetry: Digital analysis

Abstract: Background. Standard anthropometric methods applied to measurements of the skull differentials are laden with mistakes stemming from the way the measuring devices are built and from a lack of experience on the part of the researchers. To increase objectivity, digital imaging measurements via computer systems were introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
5
1
0
1
Order By: Relevance
“…The observed parameters of the orbital height and width had a tendency to be higher on the right side, leading to the higher values of the left orbital index (right: 87.75 ± 7.2, left: 90.6 ± 6.8; p = 0.0135, t test). This is in accordance with the earlier findings and widely accepted theory that the skull and the face right/left asymmetry with higher values of the right orbital measures are the consequence of the brain asymmetry and the dominance of the left hemisphere (11,23). Interestingly, the right orbital index falls well within mesoseme category, typical for the European and Caucasian race (23), whereas the left orbits were at the lower end of megaseme category (1,13,16,17).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observed parameters of the orbital height and width had a tendency to be higher on the right side, leading to the higher values of the left orbital index (right: 87.75 ± 7.2, left: 90.6 ± 6.8; p = 0.0135, t test). This is in accordance with the earlier findings and widely accepted theory that the skull and the face right/left asymmetry with higher values of the right orbital measures are the consequence of the brain asymmetry and the dominance of the left hemisphere (11,23). Interestingly, the right orbital index falls well within mesoseme category, typical for the European and Caucasian race (23), whereas the left orbits were at the lower end of megaseme category (1,13,16,17).…”
Section: Discussionsupporting
confidence: 92%
“…This appears to be a constant feature of the human race, in congruence with other body measures that are larger in men (18). The results of our study also confirmed the earlier findings in variation of orbital dimensions between the left and right side (13,23). The observed parameters of the orbital height and width had a tendency to be higher on the right side, leading to the higher values of the left orbital index (right: 87.75 ± 7.2, left: 90.6 ± 6.8; p = 0.0135, t test).…”
Section: Discussionsupporting
confidence: 91%
“…According to the values of orbital indices (right 86.5 ± 7.2 and left 90.2 ± 6.8), we could conclude that the right orbits in Serbs could be placed in mesoseme category, typical for the European and Caucasian race [24], whereas the left orbits are megaseme. Similar to the data from the Polish population [26], Serbian females had higher orbital indices (right: 90.02 and left: 91.09), which could be classified as megaseme, in comparison to the orbital indices of Serbian males. In both sexes, orbital index had tendency towards higher values on the left side, which was in males significant (p = 0.012, t-test).…”
Section: Discussionsupporting
confidence: 81%
“…Para a cavidade orbital esquerda, o formato romboide, seguido pelo retangular e pelo circular foram mais frequentes. Os resultados obtidos acerca da variabilidade dos tipos das cavidades orbitais, considerando-se a antimeria, vão ao encontro das observações de Lepich et al (2017), que verificaram que a morfologia da órbita direita era distinta da esquerda, atribuindo essa diferença à assimetria facial natural do ser humano.…”
Section: Discussionunclassified